Pengaruh Brand Equity Dan Country Of Origin Terhadap Minat Beli Produk Smartphone Samsung: (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Majalengka) - Pipih Sopiyan; Gun Gun Gumelar (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2019)
This study aims to find out how the influence of brand equity and country of origin on Samsung smartphone product purchase interest in the students of the Faculty of Economics, Majalengka University). The research method used in this study is a survey with a descriptive and verification analysis approach. The sample in this study were 100 students using probability sampling techniques with simple random sampling and sampling using the Slovin formula. Data collection techniques are questionnaires. Testing the data instrument is done by validity and reliability testing. Data analysis using correlation analysis, coefficient of determination, t test and F test). The results of the study show that for Brand Equity and Country Of Origin including good categories and buying interest including the high category. Brand Equity significantly influences consumer buying interest. Country Of Origin significantly influences consumer buying interest. Simultaneously Brand equity and Country Of origin significantly influence consumer buying interest.